# The function f o g o h for functions f ( x ) = x − 1 , g ( x ) = x and h ( x ) = x − 1 .

### Precalculus: Mathematics for Calcu...

6th Edition
Stewart + 5 others
Publisher: Cengage Learning
ISBN: 9780840068071

### Precalculus: Mathematics for Calcu...

6th Edition
Stewart + 5 others
Publisher: Cengage Learning
ISBN: 9780840068071

#### Solutions

Chapter 2.6, Problem 45E
To determine

## To find: The function fogoh for functions f(x)=x−1 , g(x)=x and h(x)=x−1 .

Expert Solution

The function fogoh for functions f(x)=x1 , g(x)=x and h(x)=x1 is equal to x11 .

### Explanation of Solution

Given information:

The functions are f(x)=x1 , g(x)=x and h(x)=x1 .

Calculation:

Simplify the function fogoh .

(fogoh)(x)=(fog)(h(x))=(fog)(x1)=f(g(x1))=f(x1)

Further simplify,

(fogoh)(x)=f(x1)=x11

Therefore, The function fogoh for functions f(x)=x1 , g(x)=x and h(x)=x1 is equal to x11 .

### Have a homework question?

Subscribe to bartleby learn! Ask subject matter experts 30 homework questions each month. Plus, you’ll have access to millions of step-by-step textbook answers!